Prolonged PR interval, first-degree heart block and adverse cardiovascular outcomes: a systematic review and meta-analysis. (15th February 2016) - Kwok, Chun Shing; Rashid, Muhammad; Beynon, Rhys; Barker, Diane; Patwala, Ashish; Morley-Davies, Adrian; Satchithananda, Duwarakan; Nolan, James; Myint, Phyo K; Buchan, Iain; Loke, Yoon K; Mamas, Mamas A
Abstract : Objective: First-degree atrioventricular block is frequently encountered in clinical practice and is generally considered a benign process. However, there is emerging evidence that prolonged PR interval may be associated with adverse outcomes. This study aims to determine if prolonged PR interval is associated with adverse cardiovascular outcomes and mortality. Methods: We searched MEDLINE and EMBASE for studies that evaluated clinical outcomes associated with prolonged and normal PR intervals. Relevant studies were pooled using random effects meta-analysis for risk of mortality, cardiovascular mortality, heart failure, coronary heart disease, atrial fibrillation and stroke or transient ischaemic attack (TIA). Sensitivity analyses were performed considering the population type and the use of adjustments. Results: Our search yielded 14 studies that were undertaken between 1972 and 2011 with 400 750 participants. Among the studies that adjusted for potential confounders, the pooled results suggest an increased risk of mortality with prolonged PR interval risk ratio (RR) 1.24 95% CI 1.02 to 1.51, five studies. Prolonged PR interval was associated with significant risk of heart failure or left ventricular dysfunction (RR 1.39 95% CI 1.18 to 1.65, three studies) and atrial fibrillation (RR 1.45 95% CI 1.23 to 1.71, eight studies) but not cardiovascular mortality, coronary heart disease or myocardial infarction or stroke or TIA. Similar observations were recorded when limited to studies of first-degree heart block. Conclusions: Data from observational studies suggests a possible association between prolonged PR interval and significant increases in atrial fibrillation, heart failure and mortality. Future prospective studies are needed to confirm the relationships reported, consider possible mechanisms and define the optimal monitoring strategy for such patients.